Does Corporate Diversification Create Value in Emerging Markets? New Evidence from Chile - Espinosa-Mendez, C (Wiley-Blackwell Publishing, 2018)
Using a sample of 85 Chilean firms listed in the Santiago Stock Exchange from 2005 to 2013, we analyze the impact of corporate diversification on firm value. We consider voting rights of the main shareholder and institutional investors’ influence on firm value. We report firm-value destruction for diversified firms. Regarding ownership concentration, we report a negative relation between the largest shareholder ownership and firm value. Separation between voting rights and cash flows rights of this shareholder is negatively related to firm value. While Pension Fund Administrators (AFP) mitigate firm value destruction in diversified firms, other institutional investors do not play an active role in controlling value destruction. Finally, if the largest owner is a family, we report firm-value creation in diversified firms. Copyright © 2016 ASAC. Published by John Wiley & Sons, Ltd. Copyright © 2016 ASAC. Published by John Wiley & Sons, Ltd.